Consideration of the Safety of Bungee Jumping in Relation to Mechanical Properties of the Installation Based on a Jump Accident in Gdynia - TOMASZEWSKA, Agnieszka; KŁOSOWSKI, Paweł (Engineering Transactions, 2022)
This paper considers a bungee jumping accident that took place in July 2019 in Gdynia, Poland. The authors conducted an investigation to determine the cause of the bungee rope failure. It was based on mechanical tests concerning the strength of the rope as well as thecalculation of the force induced in the rope during the jump. Based on the theoretical and experimental results, the rope safety factor was estimated. It appeared to be three-fold lower than it is recommended in Polish regulations concerning ropes dedicated to lifting people for industrial and public purposes. However, no law regulations strictly concerning bungee  installation makes it easy for accidents to occur.